SISTEM INFORMASI PEMASARAN RUMAH DI GRAHA PERMATA SURYA MIJEN SEMARANG BERBASIS WEB - Muhammad Fahrozi, Dedi; Diartono, Dwi Agus (Proceeding SENDI_U, 2015)
At this present moment in life as well as increasing competition in the business, it brings a hugeimpact on peoples demands for services and information fast, accurate, safe and comfortable inwhich society as a businessman and as a customer. Similarly, in the trading business, services suchas the above plays an important role. Utilizing the web is one of the alternative ways to improve theservice. By using the Web no longer limitations of space and time to obtain the requiredinformation as quickly as over the internet. This study aims to facilitate the prospective consumersin obtaining housing information quickly, easily and efficiently and build a marketing strategy tothe public housing through the web. This new web-based system to perform payment transactionsmade by means of transfers between bank accounts via ATM or through a cash deposit to theaccount number PT. Bagoes Property. After payment, the consumer is expected to confirm thepayment order into the system in order to be displayed into the financial statements that can beviewed by the owner of PT. Bagoes Property.Keywords: sisfo, pemasaran rumah, graha permata surya, mijen